Hegemony and Counter-Hegemony in Ethiopia: Imagining a Post-TPLF Order - Woldeyesus, Solomon Kassa; Endris, Mohammed Yimam (Modern Africa: Politics, History and Society, 2021)
This article examines the discursive strategies, the ideological dominations and interrelated material tools employed by the Tigray People’s Liberation Front (TPLF) in maintaining its rule. It also unravels the hegemonic crisis it has encountered, and the counter-hegemony it has confronted since 2015. Gramscian novelties of historical bloc, hegemony, organic crisis, counter-hegemony, and interregnum, are deployed in order to understand the continuities, ruptures and crises witnessed in Ethiopia’s politics for the past thirty years. The article interprets the crisis of the TPLF since the 2015 protests through the prism of organic crises and analyses the counter-hegemonic contestations, the interregnum and the ongoing war since 4 November 2020. The article adds to the recent resurgence of interest in Gramscian perspectives by demonstrating the relevance of Gramscian concepts to the understanding of politics in the states of the global south.